Contradictory Perspectives on Academic Support: Beyond Linear Logic - Hallett, Fiona (Frontiers in Education, 2021)
This paper employs a Square of Opposition as an interpretivist heuristic device in order to interrogate perceptions of academic support. The Square of Opposition is used to move beyond binary explanations of academic development subsumed within learner-/discipline-focussed practices or institutionally /epistemologically constrained systems; an exemplar data set is used to achieve this. The results of this analysis demonstrate that positions that might normally be understood as opposed in fact share common features, at least where some key concepts are concerned. In particular, two “contradictories” are explored: the first of these critiques the differences and similarities between contested meaning-making and knowledge dissemination and the second analyses the disjuncture between skills-focussed instruction and academic literacy as a social practice. This form of analysis offers new insights that directly speak to the ways in which we conceive of, and enact, teaching, personal tutoring and academic advising.